SPATIAL ANALYSIS OF THE ABANDONMENT OF AGRICULTURAL LAND IN SLOVENIA - Matjaž Glavan; Aljaž Malek; Marina Pintar; Helena Grčman (Acta Agriculturae Slovenica)
In this study we performed a spatial analysis to determine the influence of selected environmental factors (forests share, elevation a.s.l., slope, aspect, flooding) and the management status of an area on the spatial distribution of the abandoned agricultural land (land use class 1410), and agricultural land with forest trees (land use class 1800) in Slovenia. All these natural factors influence the management decisions of landowners. We found out that land use class 1410 is distributed over the entire country, along the south-west to the north-east axis. The majority of the land use class 1800 can be found in the south-western part of the country. On municipality level, the link between the forest and studied land uses was weak. The percentage of land use classes 1410 and 1800 grows with increasing altitude a.s.l. and slope. Land use class 1400 is more frequent in flooded areas. The percentage of the abandoned agricultural land is greater in areas with special management status (e.g. Natura 2000 areas). A strict, professional and fast implementation of the Agricultural Land Act is needed to improve the situation and prevent further agricultural land losses.